Evaluation of the potential removal of phosphate using rice husk ash‐derived zeolite NaP1. Issue 6 (23rd March 2023) - Tran‐Nguyen, Phuong Lan; Ly, Kim‐Phung; Nguyen, Thanh‐Ty; Santoso, Shella Permatasari; Tran, Nguyen‐Phuong‐Dung; Angkawijaya, Artik Elisa; Yuliana, Maria; Nguyen, Minh‐Nhut; Thi‐Tran‐Anh, Tuan
Abstract: BACKGROUND: Zeolite NaP1 with high crystalline intensity and good shape has been synthesized by utilizing rice husk ash. Several factors related to the formation of zeolite, such as mixing ratios, aging time, and reaction time, were investigated. Furthermore, the potential phosphate adsorption of the optimal synthesized zeolite was evaluated. RESULTS: Under the optimal conditions (SiO2 /Al2 O3 molar ratio = 4.0, NaOH concentration = 1.5 M, aging time = 12 h, and reaction time = 8 h), the surface area and pore diameter of the zeolite NaP1 obtained were 50 m 2  g −1 and 40.77 Å, respectively. By varying the aging and reaction times, zeolite NaP1 with different surface areas could be created. Specifically, reducing the aging time and reaction time result in zeolite NaP1 with a lower surface area. The adsorption efficiency and adsorption capacity of the optimal synthesized zeolite NaP1 were 38.67% and 19.97 mg g −1, respectively, at pH 6.0, with an initial phosphate concentration of 100 mg L −1, an adsorbent dosage of 2 g L −1, and a contact time of 120 min. The data are well described under the Temkin and Redlich‐Peterson models, with the correlation coefficients of 0.991 and 0.995, respectively. The maximum adsorption capacity of the Langmuir model reached 19.053 mg g −1 . CONCLUSION: The main contribution of this work is the direct use of rice husk ash without pretreatment to generate high crystalline zeolite NaP1 in a shorter time. The phosphate ion removal efficiency by zeolite NaP1 may be further improved by functionalizing zeolite surfaces and expanding its other applications. © 2023 Society of Chemical Industry (SCI).